Scada Configuration on 20kv Distribution Network in Central Java and Yogyakarta Special Region using ROPO, IDAS, and "Survalent" (International Journal of Innovative Research in Engineering & Management, 2021)
Like other SCADA systems in Central Java & DIY APD, there  are three main SCADA implementation pillars: Master Station,  Remote Terminal Unit, and Telecommunications. The Master  Station functions to manage the SCADA software and its  operational display. The remote Terminal Unit is an executor  device to control and retrieve the status of Electric Power  Distribution equipment. Meanwhile, Telecommunications is in  charge of managing communication to connect the results of the  Remote Terminal Unit with the Master Station. To optimize all three and improve the reliability of electricity  distribution PT. PLN (Persero) Distribution Control Area (APD in  Indonesian) Central Java and DIY changed the current SCADA  configuration (still separate in each region) into a centralized and  well-organized future structure. The stages of realizing the plan  include: setting up the SCADA master configuration, namely  ROPO, IDAS, and "Survalent"; Building a backup server (Quad  Redundant Server); and embodying the concept of 3 DCC.
Keywords: Configuration; SCADA; Distribution